1998
DOI: 10.1097/00005344-199800001-00026
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1, Delayed Rectifier K Channels, and Pulmonary Arterial Smooth Muscle

Abstract: Sarafotoxin S6c [STXS6c; a selective endothelin-B (ETB) receptor agonist] causes constriction of isolated pulmonary arteries. In perforated-patch experiments on pulmonary arterial myocytes, ET-1 and STXS6c induced a gradual inhibition of the delayed rectifier K current (IKV), the profile of which resembled that carried by Kv1.5. Reverse-transcriptase polymerase chain reaction (RT-PCR) experiments revealed mRNA encoding this channel, and immunolocalization experiments demonstrated expression of the channel prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…For example, several earlier studies suggested that endothelin-1 inhibits K v channels in arterial myocytes (2,36,46,51,52). The contribution of this effect to endothelin-1-induced membrane depolarization is not clear, however.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several earlier studies suggested that endothelin-1 inhibits K v channels in arterial myocytes (2,36,46,51,52). The contribution of this effect to endothelin-1-induced membrane depolarization is not clear, however.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Inward Cl − currents (due to Cl − efflux) are enhanced by α-adrenergic stimulation in rabbit portal vein myocytes (13), by endothelin-1 or angiotensin II in rat pulmonary artery myocytes (20,45,46), and by endothelin-1 or vasopressin in A7r5 cells (56). Furthermore, the stimulation of Cl − efflux has been implicated in the vasoconstrictor effects of endothelin-1 in rabbit basilar artery (10) and norepinephrine in rat resistance arteries (33) and aorta (32).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Acute up-regulation of gating by protein kinase A activated in response to isoprenaline or forskolin treatment (Aiello et al 1995(Aiello et al , 1998, and down-regulation of gating by vasoconstrictors, such as angiotensin II , endothelin-1 (Salter et al 1998), thromboxane-A 2 (Cogolludo et al 2003) acting via protein kinase C, uridine triphosphate via Rho kinase (Luykenaar et al 2004), and vasopressin via tyrosine kinase (Pyk-2) (Byron and Lucchesi 2002) have been demonstrated for VSM K DR channels. The responses are not necessarily observed in all vessels; for example, clear evidence of a vessel-specific modulation of K DR gating was obtained in experiments on cerebral arterial myocytes showing an absence of modulation by protein kinase C (PKC) activation (Luykenaar et al 2004) that is evident in cells from other vessels (Aiello et al 1996;Hayabuchi et al 2001;Cogolludo et al 2003).…”
Section: Acute Modulation Of K Dr Channel Gatingmentioning
confidence: 99%
“…One alteration induced by chronic hypoxia involves activation of an ET-1 contractile pathway that is distinct from that which is activated during normoxia. Under normoxic conditions, ET-1 causes release of Ca 2ϩ from intracellular stores, PKC-dependent inhibition of voltage-gated K ϩ (K v ) channels, and subsequent membrane depolarization and Ca 2ϩ influx through voltage-dependent calcium channels (VDCCs) (30,33,34). This increase in intracellular calcium concentration ([Ca 2ϩ ] i ), due to both influx and release, activates myosin light chain kinase (MLCK), resulting in phosphorylation of myosin light chains and contraction (39,40).…”
mentioning
confidence: 99%